Management of tennis elbow - Chesterton LS; Mallen CD; Hay EM (Dove Medical Press, 2011)
Linda S Chesterton, Christian D Mallen, Elaine M HayArthritis Research UK Primary Care Centre, Primary Care Sciences, Keele University, Keele, Staffordshire, UKDate of preparation: April 21, 2011Conflict of interest: None declaredClinical question: What is the best treatment for tennis elbow?Results: Despite a wealth of research, there is no true consensus on the most efficacious management of tennis elbow especially for effective long-term outcomes. Corticosteroid injections do show large pain-relieving effects in the short term but are associated with risks of adverse events and long-term reoccurrence. Advice with a “wait and see” approach is recommended as the first-line treatment in primary care for most cases. In the medium term physiotherapy and or low-level laser therapy may be effective.Implementation: Rule out alternative diagnosis. Onward referral may be indicated if the condition does not resolve after 12 months.Keywords: tennis elbow, corticosteroids, physiotherapy, laser therapy